2022
DOI: 10.3390/biomedicines10123071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Osteogenic Differentiation Potential of Adipose Tissue-Derived Stromal Cells and Dedifferentiated Adipose Cells of the Same Tissue Origin under Pro and Antioxidant Conditions

Abstract: Adipose tissue-derived stromal cells (ASCs) play an important role in various therapeutic approaches to bone regeneration. However, such applications become challenging when the obtained cells show a functional disorder, e.g., an impaired osteogenic differentiation potential (ODP). In addition to ASCs, human adipose tissue is also a source for another cell type with therapeutic potential, the dedifferentiated fat cells (DFATs), which can be obtained from mature adipocytes. Here, we for the first time compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…They found that both stem cell types had greater difficulty differentiating when hydrogen peroxide was introduced to the system, mimicking oxidative stress. In contrast, catalase introduction led to a 2.5-fold increase in osteogenesis in both cell types [ 85 ]. Another study by Wu et al examined the bone regeneration capacity of BM-MSCs vs. AT-MSCs under different culture conditions.…”
Section: Stem Cellsmentioning
confidence: 99%
“…They found that both stem cell types had greater difficulty differentiating when hydrogen peroxide was introduced to the system, mimicking oxidative stress. In contrast, catalase introduction led to a 2.5-fold increase in osteogenesis in both cell types [ 85 ]. Another study by Wu et al examined the bone regeneration capacity of BM-MSCs vs. AT-MSCs under different culture conditions.…”
Section: Stem Cellsmentioning
confidence: 99%
“…They found that both stem cell types had greater difficulty differentiating when hydrogen peroxide was introduced to the system, mimicking oxidative stress. In contrast, catalase introduction led to a 2.5-fold increase in osteogenesis in both cell types [84]. Another study by Wu et al examined the bone regeneration capacity of BM-MSCs vs. AT-MSCs under different culture conditions.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%